You too can succeed - Singh, Joginder (United Kingdom : New Dawn Press, Inc., 2004)
About the Book: You Too Can Succeed (3z(BYou too can succeed(3y (Bis born out of the personalexperiences and reflections of the author. Success is good timber,which does not grow with ease. This book, packed with excellentquotes, marvelous ideas and inspiration, is an insightful guide tohelp you make a mark for yourself in your chosen field. This bookshows what you can, and should do, in solving daily problems andfor leading a successful and purposeful life. One way to be happy,indeed the only way to be happy, is to have a purpose in life. Each one of us dream of success but mere dreaming is not enough.To turn your dream into reality you have to take action. Action isthe key to success. One time success is not sufficient. You need tosucceed time and again or else you will find yourself forgotten orbelittle. The ability to succeed is there in all of us. If you wanttoo can succeed. This book is a small step in helping the readers look ahead andmake the best of their lives. About the Author Joginder Singh , now retired, joined the IndianPolice Service in 1961 and rendered over thirty-six years ofservice. He is the recipient of two highest police medals formeritorious service (1995) and distinguished servics
Keywords: Self-culture.